2020
DOI: 10.1080/10408398.2020.1841090
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D deficiency aggravates COVID-19: systematic review and meta-analysis

Abstract: There is still limited evidence regarding the influence of vitamin D in people with COVID-19. In this systematic review and meta-analysis, we analyze the association between vitamin D deficiency and COVID-19 severity, via an analysis of the prevalence of vitamin D deficiency and insufficiency in people with the disease. Five online databases-Embase, PubMed, Scopus, Web of Science, ScienceDirect and pre-print Medrevix were searched. The inclusion criteria were observational studies measuring serum vitamin D in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
316
3
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(363 citation statements)
references
References 50 publications
17
316
3
27
Order By: Relevance
“…On the other hand, our promising results may justify the investigation of LF in combination with other nutraceuticals to verify their possible synergistic effects. In particular, LF has been shown to increase the expression of vitamin D receptor (VDR) in the colon of vitamin D deficient mice [ 49 ] and a growing body of evidence suggests that vitamin D deficiency may play a central role in COVID-19 pathophysiology and mortality [ 50 , 51 ]. Thus, LF and vitamin D combined supplementation may represent a valid adjuvant therapeutic tool in patients with COVID-19 in light of their well-known anti-inflammatory and immunomodulatory properties [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our promising results may justify the investigation of LF in combination with other nutraceuticals to verify their possible synergistic effects. In particular, LF has been shown to increase the expression of vitamin D receptor (VDR) in the colon of vitamin D deficient mice [ 49 ] and a growing body of evidence suggests that vitamin D deficiency may play a central role in COVID-19 pathophysiology and mortality [ 50 , 51 ]. Thus, LF and vitamin D combined supplementation may represent a valid adjuvant therapeutic tool in patients with COVID-19 in light of their well-known anti-inflammatory and immunomodulatory properties [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small observational studies and trials have shown encouraging results. For example, a retrospective study in a single center showed that the deficit of vitamin D was associated with increased COVID-19 risk [ 159 ], and a meta-analysis of 27 studies found that severe cases of COVID-19 more frequently had vitamin D deficiency compared with mild cases, while vitamin D insufficiency was associated with an increased possibility of hospitalization and mortality [ 184 ]. Another retrospective observational trial in 186 cases of severe COVID-19 found that low 25(OH)D levels on admission were associated with COVID-19 disease stage and mortality [ 185 ].…”
Section: Magnesium and Covid-19 Pandemicmentioning
confidence: 99%
“…A meta-analysis of 27 published studies reported that vitamin D insufficiency was associated with increased hospitalization (OR= 1.81, 95% CI 1.41-2.21) and increased mortality from Covid 19 (OR= 1.82, 95% CI 1.06-2.58). 6 A German study reported that serum Selenium was significantly lower in Covid 19 patients who died versus those who survived. 7 Other studies have reported better nutrition and/or supplementation with a wide range of nutrients such as Ω-3 fats, amino acids, zinc, vitamins C & E may be useful in both preventing and treating Covid 19 and other serious infections.…”
Section: Specific Nutrients May Improve Covid 19 Survivalmentioning
confidence: 99%